2020
DOI: 10.1093/arclin/acaa097
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Telephone Neuropsychological Assessment

Abstract: Objective Telephone-based neuropsychological assessment (TeleNP) has been shown to be a valid alternative to in-person or video-based assessment. However, there is limited information regarding patients’ satisfaction with TeleNP. This report presents satisfaction survey data from a diverse, clinical sample who received TeleNP during the coronavirus disease pandemic. Method A total of 43 adult patients (30.2% Hispanic/Latinx, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Patients underwent a telephone-based neuropsychological assessment battery; telephone assessment has been shown to be feasible and provides valid assessment of cognitive function relative to in-person exams( (24) , (25) , (26) ). This battery has been successfully implemented in diverse patient populations( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients underwent a telephone-based neuropsychological assessment battery; telephone assessment has been shown to be feasible and provides valid assessment of cognitive function relative to in-person exams( (24) , (25) , (26) ). This battery has been successfully implemented in diverse patient populations( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple patient experience studies have consistently reported difficulties in communicating or connecting with providers during telehealth visits [3,6]. A desire for building an improved rapport with their providers is one of the most popular reasons why many patients prefer in-person visits [20]. In particular, the establishment of primary care or the initial consultation, similar to a first date, may not be welcomed by all and could negatively affect patient experience or the development of a sense of "my doctor."…”
Section: Unintended Consequences Of Telehealthmentioning
confidence: 99%
“…Even among persons with internet access, criticism of TeleNP has been raised based on research showing that reliability and validity of TeleNP are impacted by patient characteristics (e.g., age, comfort and familiarity with computers) and technology factors such as monitor size, screen resolution, and internet speed (Brearly et al, 2017;Hirko et al, 2020). These access barriers have led to deeper consideration of TeleNP via telephone (Caze et al, 2020;Lacritz et al, 2020). Indeed, TeleNP via telephone has been effectively utilized in research settings dating back to the 1980s and continuing to present day (Brandt et al, 1988;Bunker et al, 2017;Castanho, Amorim, Zihl, Palha, Sousa, Santos, 2014;Castanho et al, 2016;Matchanova et al, 2020;Nelson et al, 2020;Pendlebury, Welch, Cuthbertson, Mariz, Mehta, & Rothwell, 2013;Plassman, Newman, Welsh, & Helms, 1994).…”
Section: Neuropsychological Testing and Telehealthmentioning
confidence: 99%